Penggunaan variasi bahasa gaul pada mahasiswa prodi bsa uin malang tahun 2025: kajian sosiolinguistik - Putri, Dwi Ananda (Maliki Interdisciplinary Journal, 2026)
This article explores the use of slang language among students of the Arabic Language and Literature Department at UIN Maulana Malik Ibrahim Malang in 2025 from a sociolinguistic perspective. The research aims to describe the forms and meanings of slang expressions commonly used in daily conversations, and to analyze the social factors that influence their usage. Using a qualitative descriptive method, data were collected through interviews, observations, and literature review. The findings reveal 20 slang words categorized into eight types, such as informal pronouns, English acronyms, phonetic alterations, and local dialect borrowings. The results show that slang among students is not merely linguistic deviation but reflects cultural adaptation, digital influence, and youth identity in social interactions. This research contributes to the sociolinguistic understanding of language variation among university students.